LANGUAGE SYNTAX ERROR ANALYSIS ON THE ESSAY CONTEST PARTICIPANTS IN THE 25th PRACTICAL LITERATURE AT UNIVERSITY OF RIAU YEAR 2017 - Elvrin Septyanti (Jurnal Didascein Bahasa, 2017)
This research aims to analyze the syntax errors on writing essays to 25 practical literature participants in academic year2017 at FKIP University of Riau. It used qualitative descriptive. Source of research data obtained based on the collection of essays writing from participant contests. The data was taken from the language syntax errors analysis between phrases to phrase and clauses to clauses. The researcher used documentation as the technique such as reading collection of essays, classifying error analysis of language syntax, and analyzing the essays of participants. The pproceduress were: (1) selecting the language corpus, (2) identifying the errors in the corpus, (3) classifying the errors, (4) explaining the errors, and (5) evaluating the errors. There were 38 data with errors on phrases which include the addition of phrases in the object (B+S) were 15 data, the addition of words from or about in the phrase objects (B+B) were 3 data, the additional of words to Work in phrases (passive K+K) were 12 data and errors on the clause, and the additional of the preposition words between verbs and its object in clause were 8 active data.Keywords: Field of language syntax error, teaching literature, essays.